Analisis uji beda pendapatan nelayan purse seine berdasarkan ukuran kapal di tempat pelelangan ikan sodohoa Kota Kendari - Wahid, Andi; Nurdiana A; Piliana, Wa Ode; La Ola, Onu; Kamri, Syamsul; Daeng Siang, Roslindah; Sriwulan, Desy (Jurnal Sosial Ekonomi Perikanan, 2022)
This study aims to compare the income of purse seine fishermen based on the size of the vessel at the Sodohoa Fish Auction Port, West Kendari District, Kendari City. This research was conducted from November to December 2020. The method in this study is the fraction per cluster sampling method with a total sample of 10 people using ships above 30GT and 10 people using ships under 30GT. Data obtained through interviews using a questionnaire. The data obtained were analyzed using the formula for total costs, revenues, profits and t-test to compare the income of purse seine fishermen. From the results of the analysis, it is known that the profit of purse seine fishermen who use vessels under 30GT is IDR20,175,778/catch and the profit of purse seine fishermen who use vessels above 30GT is IDR24,125,541/catch. Based on the above analysis, it is known that the level of difference in the income of purse seine fishermen who use vessels above 30GT and below 30GT is IDR3,949,763/catch. Based on the t-test analysis using SPSS, it is known that the significance value is 0.331 and greater than 0.05, meaning Ho is accepted, meaning that there is a difference in profits between purse seine fishermen based on the size at the Sodoha Fish Auction Port, Kendari City.